Student Registration System for SMK Bandar Sungai Petani - PADMANADHAN, PUGALENTHREN; Ahmad Khalid, Shamsul Kamal (Applied Information Technology And Computer Science, 2023)
Student registration system for SMK Bandar Sungai Petani aims to create a student management system with role-based access control, encrypted database, and dual authentication. The student welfare members will be the admin of this system and they can add others as admins and add staffs into the system. The staffs are allowed to register students into the system by entering the students’ details. Only those students who have been allowed by the admins will be registered into the system. When logging in, users need to enter their username and password as first factor authentication and need to enter an OTP sent to their email as second factor authentication. This feature is to make sure only allowed personnel get access to the system and to secure the system from getting breached by attackers.